1978
DOI: 10.1002/jcp.1040960206
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyglucose and 3‐O‐methylglucose transport in untreated and ATP‐depleted novikoff rat hepatoma cells. Analysis by a rapid kinetic technique, relationship to phosphorylation and effects of inhibitors

Abstract: Detailed time courses of uptake of labeled 3-O-methyl-D-glucose and 2-deoxy-D-glycose by untreated and ATP-depleted Novikoff rat hepatoma cells were determined as function of concentration (0.2-10 mM) by a rapid mixing/sampling technique which allows uptake measurements in time intervals as short as 1.5 seconds. Intracellular accumulation of 3-O-methylglucose in untreated and ATP-depleted cells and of deoxyglucose in ATP-depleted cells to equilibrium followed pseudo-first order kinetics and initial velocities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Hence the differences between 2-DOG and 3-O-MG uptake and K m could be explained by the phosphorylation of 2-DOG by hexokinase. Higher K m values were observed when 3-O-MG was used ; this has been reported by other investigators using other cell types [32][33][34][35][36]. Differences in uptake between the two hexoses were also observed and these would have contributed to the differences in V max .…”
Section: Discussionsupporting
confidence: 77%
“…Hence the differences between 2-DOG and 3-O-MG uptake and K m could be explained by the phosphorylation of 2-DOG by hexokinase. Higher K m values were observed when 3-O-MG was used ; this has been reported by other investigators using other cell types [32][33][34][35][36]. Differences in uptake between the two hexoses were also observed and these would have contributed to the differences in V max .…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings have been observed in rat adipocytes (Olefsky, 1978). On the other hand, mouse 3T3 cells and Novikoff rat hepatoma cells are found to contain significant steady-state levels of free intracellular 2-DOG at early times during uptake, indicating that phosphorylation, not transport, is the rate-limiting step of 2-DOG uptake (Colby and Romano, 1975;Romano, 1976;Graff et al, 1978).…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies indicate that hexose transport is the rate-limiting step in rat adipocytes (Olefsky, 1978) and L6 myoblasts (Lo and Duronio, 1984a;Klip et al, 1982). In mouse 3T3 cells and Novikoff rat hepatoma cells, though, phosphorylation was shown to be the rate-limiting step (Romano, 1976;Graff et al, 1978). In this article we provide a detailed investigation to demonstrate that transport is the rate-limiting step of hexose uptake into L6 cells.…”
mentioning
confidence: 90%
“…The rate of HMP was a measure of the extent of redutive metabolism in the cells. The HMP had been shown to increase in the presence of MISO (Varnes et al, 1984 (Graff et al, 1978;Weber, 1973), which had been shown to be selective and phloretinsensitive (Ling & Sutherland, 1986a). As shown in Figure 1, the initial rate of this transport in EMT6/Ro cells was also directly dependent on the extracellular concentration up to 5 mm glucose.…”
Section: Discussionmentioning
confidence: 99%